Supporting Latino communities' natural helpers: a case study of promotoras in a research capacity building course. - Otiniano, Angie Denisse; Carroll-Scott, Amy; Toy, Peggy; Wallace, Steven P (Journal of immigrant and minority health / Center for Minority Public Health, 2012)
Promotores have unique access to underserved and hard-to-reach Latino communities facing health disparities. Although promotores are involved in community change, they rarely receive training that gives them the skills to be partners in research. We present a case study of promotoras who participated in a research capacity building course focused on assessing community health needs. Data comes from course application surveys, follow-up notes, and narratives from qualitative phone interviews of eight promotoras. Content analysis drawing from grounded theory was conducted to identify and describe emerging themes. Four themes emerged as promotoras discussed their experience learning basic research skills and teaching others: (1) challenges, (2) support, (3) building capacity, and (4) using research. Promotores play an important role in the health of Latino communities and are increasingly asked to participate in research processes; however they have few opportunities for training and professional development in this area. Capacity building opportunities for promotores need to be tailored to their needs and provide them with support. Fostering collaboration between promotores and partnering with local community-based organizations can help facilitate needed research skill-building among promotores.
Keywords: Capacity Building; Community Health Workers; Community-Based Participatory Research; Health Status Disparities; Hispanic Americans; Humans; Interviews as Topic; Needs Assessment; Organizational Case Studies; Qualitative Research